RADIKALISME AGAMA PERSPEKTIF AL-QUR’AN - Hamdan Hidayat (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2021)
One of the causes of the radical ideology adhered to by a group of religious organizations is that it comes from an understanding of the text that comes from the Koran or the hadith which is less comprehensive, partial, and fundamental, resulting in the misuse of arguments to justify the group, it is easy to blame people who are outside his line of thought, and making the text as legitimacy that radical acts carried out with violence are legal because they are commands of Allah listed in the holy book, but in essence God does not order actions that can harm other people. In general, the actions taken by radicals are aimed at purifying religious teachings, because they consider that there are many deviations that leave Islam, and to rectify them by fighting and destroying all these deviant actions. In this article, we will explain how the Qur'an talks about radical acts carried out with violence by looking at several verses in certain surahs and then contextualizing them with reality so that it will open knowledge about the real radicals.